THE ROLE OF VIRTUAL SIMULATION AND ONLINE LEARNING IN ADVANCING MEDICAL EDUCATION AMONG THE YOUTH POPULATION OF PAKISTAN - Dr. Saelah Amin; Dr. Naheed Akhtar; Dr. Hareem; Dr. Nadeem Akhtar Korai; Dr. Muhammad Aitmaud Uddolah Khan; Dr. Shazia Azhar (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: The pandemic has brought to light the students' need for online learning and virtual simulations.Objective: To evaluate the role of Virtual Simulation and Online Learning in Advancing Medical Education in PakistanMethods: Almost 90 medical students were enrolled at one of Pakistan's private medical universities. The students were placed in two groups. Group A had only those students who took traditional learning, and Group B had students who took both online education and virtual simulation. The independent-sample t-test was used to compare the outcomes of the two groups.Results: Out of 90 students, 28 (31%) were male students and 62 (68%) were female students. Almost 31 (34%) students were from pre-clinical years, and 59 (65%) students participated from clinical years. Nearly 12 (13%) of the students had basic knowledge, 16 (17%) had general knowledge, and 62 (68%) had professional knowledge regarding computer skills. Further, the results revealed that there was no significant difference between the two groups (P = 0.721)Conclusion: The study's results indicate that the integrated learning strategy, which combines virtual simulation and online learning, will help students grasp the theoretical and practical components of advanced medical education.